CLINICAL SIGNIFICANCE OF IgG ANTIBODIES IN THE DIAGNOSIS OF ALLERGIC CONDITIONS AND CONTROL OF ALLERGEN-SPECIFIC IMMUNOTHERAPY. Review - I.V. Marushko; B.L. Halushko; S.D. Yuriev; T.V. Hyshchak; E.D . Moskovenko (Медична наука України, 2021)
Relevance. In recent years, there has been a significant increase in the number of allergic diseases among the population. In patients with allergic conditions in the presence of indications, allergists are increasingly prescribing allergen-specific immunotherapy. This necessitates the search for new accurate tools and markers for forecasting and evaluating its effectiveness. At present, methods of monitoring the effectiveness of allergen-specific immunotherapy are largely based on the assessment of the clinical condition of patients through questionnaires and provocative trials. Promising in this direction is the study of the role of IgG4 in the development of tolerance to allergens, and the mechanisms by which this protective function is realized. Particularly important are pathological reactions to food, which can be mediated not only by IgE, but also by IgG-associated circulating immune complexes. Therefore, it is important to study the role of IgG in the development of food intolerance and the possibility of using an elimination diet based on the identification of specific IgG to food in such patients.